Determination of α1-acid glycoprotein (AGP) concentration by HPLC in patients following local infiltration analgesia for primary total hip arthroplasty and its relation to ropivacaine (total and unbound) - Abbas, Muhammad; Alossaimi, Manal A.; Altamimi, Abdulmalik S. A.; Alajaji, Mai; Watson, David G.; Shah, Sayyed I.; Shah, Yasar; Anwar, Mohammad S. (Frontiers in Pharmacology, 2023)
Abstract Introduction: This study was performed to determine the levels α1-Acid protein (AGP) in old age patients undergoing total hip arthroplasty. α1-Acid protein (AGP) are considered as Acute phase proteins produced during the acute phase reaction in the body to various stimuli and thus their proper monitoring is important. Methods: In order to study how AGP concentrations of old age patient changes in response to surgical stress (total hip arthroplasty), a high performance liquid chromatography assay for the measurement of AGP levels was performed. AGP was isolated from the plasma by addition of perchloric acid and the analysis was carried out using PLRP-S 4000 °A column. The mobile phase consisted of 1ml TFA/L of water (solvent A pH 2) and 1ml TFA/L of acetonitrile (Solvent B). The gradient used was as follows: 0 min 18% B and 82% A, 15 min 60% B and 40% A, 17 min 60% B and 40% A followed by column re-equilibration for 7 min before the next injection. The peak for AGP was obtained between 8.8 and 8.9 minutes. The method was fully optimised according to established guidelines. Results: The data obtained was analysed on chromquest software. The AGP concentrations were determined in all samples including baseline and samples taken at different timed interval. The peak for AGP was obtained between 8.8 and 8.9 minutes for both standard AGP and in patient plasma.The graphs indicated that AGP concentration in almost all patients samples increased considerably taken especially after 4 hours and 24 hours, e.g In patient 1 initial concentration is 10.36 mg/100ml but after 24 hours its increases to 23.50 mg/100ml. So there is almost 13 mg/100ml increase in 24 hours, which is confirmation of the fact that AGP concentration increases after various conditions including surgical conditions. The increased plasma protein binding was associated comparatively to the unchanged free fraction of the drug. Conclusion: This surgical induced increase in the concentration of AGP resulted in increased of plasma protein binding of the drug (ropivacaine) which in turn keeps the free portion of ropivacaine stable during the postoperative period.